Does severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) cause orchitis in patients with coronavirus disease 2019 (COVID-19)?. Issue 3 (2nd July 2020) - Alkhatatbeh, Hassan; Alzaghari, Dima; Alkhashman, Abdelrazaq; Azab, Mohammed; Edwan, Ghazi M. Al; Abufaraj, Mohammad
ABSTRACT: Objectives: To assess the prevalence of clinical orchitis in patients with coronavirus disease 2019 (COVID-19). Patients and methods: This was a retrospective clinical observational study using data of male patients who were admitted to hospital with COVID-19 confirmed by reverse transcriptase polymerase chain reaction testing between 1 March and 4 May 2020. Patients were categorised according to age groups and disease severity. Sociodemographic information and general clinical symptoms of COVID-19 and orchitis were collected. Results: We identified a total of 253 male patients, with a mean (range) age 43 (1–78) years. Patients were followed-up until their recovery or for 21 days. We did not observe any symptoms or signs of orchitis in any patient during follow-up across all age groups and different disease status. Conclusion: Although we did not identify any patients with COVID-19 with symptoms or signs of orchitis, such an association cannot be excluded, and further studies are needed to validate our hypothesis and exclude any association at a molecular level. Abbreviations: ACE2: Angiotensin-converting enzyme 2; COVID-19: coronavirus disease 2019; CRP: C-reactive protein; ESR: erythrocyte sedimentation rate; HIV: human immunodeficiency virus; IRB, Institutional Review Board; ISH, in situ hybridisation; RT-PCR: reverse transcriptase-PCR; SARS-CoV-2, severe acute respiratory syndrome coronavirus-2; TMPRSS2: transmembrane protease, serine 2; WBC: white blood cell